28.6k views
4 votes
Which quadratic equation is equivalent to (x^2-1)^2-11(x^2-1)+24=0

Which quadratic equation is equivalent to (x^2-1)^2-11(x^2-1)+24=0-example-1

2 Answers

0 votes

Answer:

u² - 11u + 24 = 0 is equivalent to (x²-1)² - 11(x²-1) + 24 = 0

Explanation:

(x²-1)² - 11(x²-1) + 24 = 0

Evaluate each equation by substituting the value of u to match the equation above.

1) u² - 11u + 24 = 0 where u = (x² - 1)

(x²-1)² - 11(x²-1) + 24 = 0

This equation matches (x²-1)² - 11(x²-1) + 24 = 0

2) (u²)² - 11(u²) + 24 where u = (x² - 1)

[(x²-1)²]² - 11(x²-1)² + 24

This equation does not match (x²-1)² - 11(x²-1) + 24 = 0

3) u² + 1 - 11u +24 = 0 where u = (x² - 1)

(x² - 1)² + 1 - 11(x²-1) + 24 = 0

This equation does not match (x²-1)² - 11(x²-1) + 24 = 0

4) (u² - 1)² - 11(u² - 1) + 24 where u = (x² - 1)

[(x²-1)²-1]² - 11(u² - 1)² + 24

This equation does not match (x²-1)² - 11(x²-1) + 24 = 0

Therefore, the first quadratic equation is equivalent to (x²-1)² - 11(x²-1) + 24 =0.

!!

User Maryokhin
by
4.8k points
6 votes

Answer:

The correct answer is first option

u² - 11u + 24 = 0

When u = (x² - 1)

Explanation:

It is given that,

(x² - 1)² - (x² - 1) + 24 = 0

To find the correct answer

Substitute u = x² - 1

The equation becomes,

u² - 11u + 24 = 0 Where u = (x² - 1)

Therefore the correct answer is first option

u² - 11u + 24 = 0

When u = (x² - 1)

User Justin Abrahms
by
5.6k points